A Penilaian Manfaat Ekonomi Wisata Pantai Karangjahe Kabupaten Rembang Dengan Travel Cost Method - Abdillah, Rangga Fajar; Bambang, Azis Nur; Putra, Rizal Ichsan (Environmental Science Program, Ivet University, 2020)
Giving environmental value (valuation) is needed in knowing or estimating the value of environmental goods and services in an area. Karang Jahe Beach is a white sand beach tour that extends around 1.5 km located in the Punjulharjo Village, Rembang District, Rembang Regency which has its own uniqueness compared to other beaches in Rembang Regency. The purpose of this study was to determine the value of the intangible economic benefits of natural resources and the environment of Karangjahe Beach as a tourist destination. This research uses quantitative research methods, namely the Travel Cost Method (TCM) and uses logistic regression. The results of this study were obtained from the value of the intangible economic benefits of natural resources and the environment of Karangjahe Beach amounting to Rp 35,785,452,750, per year.With the value of the intangible economic benefits of natural resources and the environment of the Karangjahe Beach that is so large it is expected that the management and relevant stakeholders can realize and maintain the environment in Karangjahe Beach to be sustainable and become a tourist destination with environmental insight. Keywords: Travel Cost Method, Economic valuation, Karangjahe Beach.